OP11 Accordance with the Dietary Approaches to Stop Hypertension eating plan in the United Kingdom: an observational study using data from the National Diet and Nutrition Survey (2008–2011). (2nd September 2014) - Jones, NRV; Monsivais, P
Abstract : Background: The Dietary Approaches to Stop Hypertension (DASH) eating plan, developed by the National Institutes of Health in the USA, has been shown in both observational and experimental studies to reduce blood pressure, prevent chronic disease and reduce body weight. Despite its effectiveness it has not been promoted in the UK, although previous work has shown its cultural appropriateness and effectiveness in reducing blood pressure in a UK sample. In this study we characterised accordance with the DASH diet in a representative UK sample for the first time. Methods: We analysed the four-day dietary intakes of 1491 adults (650 men, 841 women) included in years 1–3 of the rolling programme of the National Diet and Nutrition Survey (NDNS). We assessed DASH accordance using a score that has been shown to be strongly associated with disease incidence. To derive this accordance score we ranked NDNS participants by intake of eight foods and nutrients, adjusted for energy, and assigned between one and five points for each food/nutrient group based on their consumption quintile. These points were summed to create the final score with a range between eight (least accordant) to 40 (most accordant). We used survey-weighted linear regression to estimate mean age-adjusted accordance scores for men and women and estimated sex-adjusted scores for a range of age-groups. Age- and sex-adjusted accordance scores were estimated for three different indicators of individual-level socio-economic status: household income, occupational class and qualification level. Results: The mean DASH accordance score for the population was 24.9 (standard deviation 5.6), and was significantly higher in women (mean 25.8, 95% CI 25.5–26.2) than men (mean 23.6, 95% CI 23.2–23.9). DASH accordance varied by age group, with those aged 19–34 years the least DASH accordant (mean 22.4, 95% CI 21.9–22.9) and those aged 55–64 the most (mean 26.6, 95% CI 25.9–27.2). DASH accordance was significantly higher in higher socio-economic status (SES) groups and lower in lower SES groups across all three measures of SES. The greatest difference between the highest and lowest categories was in occupational class (27.4 vs. 21.5 in the highest versus lowest groups, respectively) and the least in household income (26.5 vs. 23.1). Conclusion: Accordance with the DASH diet varies by demographic and socio-economic characteristics in the UK population, revealing a social gradient in diet quality. Promoting the adoption of DASH diets could be part of a broader, population-based approach to prevent chronic disease but the observed gradient indicates that barriers may exist to the adoption of DASH diets.